Morpho-chemical characterization of new confectionery sunflower (Helianthus annuus L.) genotypes from Argentina - Sandrinelli Tesán, Rebeca; Alvarez, Daniel; Silva, Mercedes Pilar; Aguilar, Roxana; Pazos, Adriana Alejandra; Balzarini, Mónica; Martinez, Maria Jose (Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2023)
Argentina is the world’s leading exporter of confectionery sunflower. This work characterized the morphometric and nutritional composition of sunflower seeds from new confectionery genotypes. Average morphometric variables per seed were: weight 0.11 and 0.06 g with and without achene, respectively; length 15.2 mm; and width 8.50 mm, with most calibers greater than 9.51 mm. Proximate analysis indicated that seeds without shell were an important source of lipids (49 %), as well as proteins (28 %), carbohydrates (11 %), and minerals (4.8 % ashes). Fatty acid composition showed that polyunsaturated fatty acids were the major components (56 %), followed by monounsaturated ones (34 %), and saturated ones (11 %). The mid-oleic genotype developed by INTA showed significantly greater oleic acid (47 %) and lower linoleic acid (42 %) than the commercial hybrid. Proteic composition showed 33 % of essential amino acids (EAA) while fiber and sugars represented 3.9 % and 7.3 % respectively; macroelements such as K, Mg and Ca, and microelements such as Mn, Fe, Cu, Zn, Se, Co, Mo and Na. New confectionery sunflower hybrids developed by INTA stand out for their high quality in edible oil, proteins and essential components, all very valuable for the food industry.